Influence of loading condition and reinforcement size on the concrete/reinforcement bond strength - Turk, K; Caliskan, S; Yildirim, MS (Techno-Press, 2005)
The paper reports on a study of bond strength between reduced-water-content concrete and tensile reinforcement in spliced mode. Three different diameters (12, 16 and 22 mm) of tensile steel were spliced in the constant moment zone, where there were two bars of same size in tension. For each diameter of reinforcement, a total of nine beams (1900 x 270 x 180 mm) were tested, of which three beams were with no axial force (positive bending) and the other six beams were with axial force (combined bending). The splice length was selected so that bars would fail in bond, splitting the concrete cover in the splice region, before reaching the yield point. It was found that there was a considerable size effect in the experimental results, i.e., as the diameter of the reinforcement reduced the bond strength and the deflection recorded at the midspan increased significantly, whilst the stiffness of the beams reduced. It was also found for all reinforcement sizes that higher bond strength and stiffness were obtained for beams tested in combined bending than that of the beams tested in positive bending only.
Keywords: bond strength; tensile reinforcement; size effect; lap splice; combined bending; load-deflection stiffness